Inverse Problems for Parabolic Differential Equations from Control Theory - Mohammed Al Horani (Bruno Pini Mathematical Analysis Seminar, 2015)
We are concerned with some inverse problems related to parabolic first-order and second order linear differential equations in Hilbert spaces. All the results apply well to inverse problems for partial differential equations from mathematical physics and optimal control theory. Various concrete examples are described.